Job Involvement and Innovative Work Behaviour: The Role of Learning Agility as Mediation - Veronika Agustini Srimulyani (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
The main factor in achieving organizational success in a competitive environment is innovation, and the idea of innovation in the organization is largely generated by human resources behaving innovatively. The purpose of this study is to explore the effect of job involvement (JI) on innovative work behaviour (IWB) by highlighting learning agility (LA) as mediation. The research hypothesis was tested using a sample of 109 permanent employees of PT KAI Operating Area 7 Madiun. The test results reveal that JI can significantly increase LA, and LA can significantly increase IWB. In addition, the test results also show that JI can increase IWB through learning agility which acts as full mediating. The findings of this study provide an additional literature review of the role of individuals in organizations in improving innovation in organizations through employee job involvement and employee agility in learning about job demands due to the dynamics of a highly dynamic organizational environment. These findings are consistent with the individual adaptability theory (I-ADAPT) which describes that an individual's innovative behaviour is the result of individuals in organizations having agility in learning. Learning agility can be significantly improved when the individual has a high job involvement.